“Vai ter que aturar” mulheres-políticas-negras-faveladas na Alerj - Cunha, Mirila Greicy Bittencourt (2024)
The thesis is oriented by the hypothesis: i. the entry of black women faveladas/peripherical in politics disturbs the “narcissistic pact” (BENTO, 2002) of white men, majority group in Brazilian representative democracy, heirs to the positions of power since the processes of the colonial enterprise; ii. the parliamentary activity of “women- politicians-black-faveladas”, as they are here defined, is a constant process of aquilombamento (NASCIMENTO, 2006; 2015) in the political-public sphere, that redefines it. It is proposed here a sociological analysis of the “way of making politics” presented by the Agenda Marielle Franco (INSTITUTO MARIELLE FRANCO, 2020), arranged in seven guidelines and practices, as an incitive and guide for the candidacy of black women. As is known, the councilwoman (vereadora) from Rio de Janeiro Marielle Franco was a victim of “political femicide” (SOUZA, 2020) in March 14, 2018. However, she left as a legacy another way of power organization, that we sought to verify in the activities of Dani Monteiro, Mônica Francisco and Renata Souza, her advisors, elected Federal Deputies (Deputadas Federais) in their first elections six months after the summary execution of their inspirational figure. As methodological strategy, parliamentary pronouncements were selected, made in pulpit of the plenary tribune of the Legislative Assembly of the State of Rio de Janeiro (Alerj) registered by shorthand, available on the institution’s website as “order of the day” and “discourse” (ordinary and extraordinary). With the keyword “Mariele Franco” 70 documents were filtered, of a total of 179, in the year 2019. Said speeches point, on one side, the Racist Sexist Political Violence[s] (VPSRs) (MATOS, 2019; 2021) and the confirmation of whiteness as means of domination (BENTO, 2002; CARDOSO, 2008; SCHUCMAN, 2012), on the other, the resistance of the “mulheres-negras-periféricas-faveladas”, by pronouncements, that also were escrevivências (EVARISTO, 2005; 2009; 2017; 2022). The motto of Marielle Franco’s first and only campaign, “I am because we are”, ubuntu, African proverb, echoes Brazil’s historical social construction, leaving explicit the racism, sexism, and classism that affect, until today, the public offices representative of institutional politics, confronted by them in the struggle for the decolonization of power capable of denouncing and challenging and the formal and exclusionary democracy